Patrimônio ferroviário em Uberaba: preservação e usos - Souza, Daniela Velludo de (2023)
Railway heritage played a key role in the origin of several cities, urban expansion, economic development and mobility, interconnecting several regions. Old railway complexes are highly vulnerable, with constant risks that could lead to their loss or abandonment. In this context, the dissertation started from the problem related to the preservation and uses of railway heritage in Uberaba. This study analyzed the historical trajectory of the city's railway lines, with interest in the Companhia Mogiana de Estrada de Ferro - CMEF, the Estrada de Ferro Oeste de Minas - EFOM and also in the policy of preserving railway complexes. The objective of the research was to generate subsidies to improve the preservation of Uberaba's railway heritage, taking into account the remaining architectural complex and its forms of appropriation by the local community and to encourage debate regarding this topic. Therefore, it is important that the public preservation policy at the municipal level is articulated with the state and national policy for the preservation of railway heritage, work that has been developed by the National Historical and Artistic Heritage Institute - IPHAN together with the working groups of the railway heritage. The methodology has a qualitative approach and the bibliographic research was carried out through books, theses, dissertations and articles. In the documentary analysis, newspaper reports, maps and photographs were collected from the collection of the Department of Promotion of Culture and Historical Heritage of the Uberaba Cultural Foundation - FCU, the Planning Secretariat - SEPLAN and the Uberaba Public Archive Superintendency. To verify the uses and perceptions of the railway remains in the municipality, questionnaires were administered to people who live, work and/or frequent the places. In this sense, the results contributed to a broader understanding of the various aspects linked to the preservation of railway heritage through uses.